2019
DOI: 10.15443/rl2918
|View full text |Cite
|
Sign up to set email alerts
|

El sistema de valoración como herramienta teórico-metodológica para el estudio social e ideológico del discurso

Abstract: Resumen: El propósito principal de este artículo es presentar un modelo teóricometodológico de estudios del discurso desde una perspectiva social e ideológica y precisar el papel de los recursos interpersonales del lenguaje para dar cuenta de la explicación de fenómenos sociales. De manera particular se describe y explica el potencial analítico que ofrece el sistema de valoración (Martin & White, 2005; Oteíza & Pinuer, 2012; Oteíza, 2017a) para los estudios del discurso. Con el objeto de dar cuenta de una mane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
0
7
0
6
Order By: Relevance
“…The quantification of time scope expressed by the adjective is indicating a period of time that is larger than it should be considering the situation expressed by the co-text (detainees undergoing situations of torture). Considering this, we can identify an evoked negative appreciation of integrity (see note 1), in the discourse-semantic system of attitude , over the situation described (Oteíza, 2019; Oteíza and Pinuer, 2019). By conferring extreme degree to the quality expressed by the adjective, the suffix is amplifying both: graduation in terms of time scope and negative evoked attitude in terms of appreciation.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantification of time scope expressed by the adjective is indicating a period of time that is larger than it should be considering the situation expressed by the co-text (detainees undergoing situations of torture). Considering this, we can identify an evoked negative appreciation of integrity (see note 1), in the discourse-semantic system of attitude , over the situation described (Oteíza, 2019; Oteíza and Pinuer, 2019). By conferring extreme degree to the quality expressed by the adjective, the suffix is amplifying both: graduation in terms of time scope and negative evoked attitude in terms of appreciation.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…There are only partial and initial descriptions of appraisal resources for the Spanish language. In particular, this contribution has been done by discourse analysts who have applied the system of appraisal to their written or spoken corpora in Spanish language, providing some elaborations of new categories of the sub-system of attitude (Fernández, 2017; Oteíza, 2017, 2019; Oteíza and Pinuer, 2019), proposing new graduation categories for force as quantification and intensification of chronological and metaphorical meanings of time (Oteíza and Pinuer, 2013), applying the appraisal system to different language contexts from a critical and social discourse analysis perspective (Achugar, 2016; Kaplan, 2007; Oteíza and Castro, 2019; Oteíza and Pinuer, 2016; Pascual, 2017), conducting comparative analysis between languages from a corpus linguistics approach (Carretero and Taboada, 2014; Taboaba et al, 2014), or advancing interpersonal descriptions of the Spanish Mood system at the lexicogrammatical stratum (Lavid et al, 2010; Quiroz, 2018). These studies have proven to be valuable explorations in the Spanish language because they have demonstrated that, at a higher level of functioning, the interpersonal categories of graduation proposed in the model by Martin, White and colleagues are a useful set of analytical tools for identifying authors’ graduated attitudinal positionings in different fields and genres in written and oral Spanish language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La actitud tiene como elemento central los sentimientos que se negocian en un discurso y se expresan de tres maneras: como afectos por parte de actores humanos que se presentan como productores o sintientes de una emoción; como juicios sobre el comportamiento de las personas, su capacidad para llevar a cabo una actividad, su integridad ética o de valor, así como la normalidad y determinación que pueda tener un actor en un discurso particular; y como apreciaciones respecto a ideas, cosas o hecho. El conjunto de estas formas de expresión de los sentimientos configura el ámbito semántico de la actitud y sus tres subsistemas: afecto, juicio y apreciación (Martin & White, 2005;Oteíza, 2019).…”
Section: Discurso Y Valoraciónunclassified
“…Las herramientas del sistema de valoración han resultado productivas para los analistas del discurso, especialmente para quienes trabajan desde una perspectiva crítica, en tanto permite relevar las posturas ideológicas que se (des) legitiman en los diversos intercambios lingüísticos en la vida social, colaborando con un mayor entendimiento de los fenómenos sociales (Oteíza y Pinuer 2019). Este sistema ha sido ampliamente aplicado en Latinoamérica, entre analistas críticos del discurso que trabajan en el campo de la memoria en períodos de dictadura (Achugar 2008(Achugar , 2016Oteíza 2009Oteíza , 2011Giudice 2010;Oteíza y Pinuer 2012 y también en la representación de la violación de los derechos humanos y los conflictos armados en la prensa (Bolívar 2007;Kaplan 2012;Pascual 2014Pascual , 2017.…”
Section: Introductionunclassified